Motion-corrected cardiac MRI is associated with decreased anesthesia exposure in children. - Christopher, Adam B.; Quinn, Rachel E.; Zoulfagharian, Sara; Matisoff, Andrew J.; Cross, Russell R.; Xue, Hui; Campbell-Washburn, Adrienne; Olivieri, Laura J. (Pediatric Radiology, 2020)
Background: The benefits of cardiac magnetic resonance imaging (MRI) in the pediatric population must be balanced with the risk and cost of anesthesia. Segmented imaging using multiple averages attempts to avoid breath-holds requiring general anesthesia; however, cardiorespiratory artifacts and prolonged scan times limit its use. Thus, breath-held imaging with general anesthesia is used in many pediatric centers. The advent of free-breathing, motion-corrected (MOCO) cines by real-time re-binned reconstruction offers reduced anesthesia exposure without compromising image quality.Objective: This study evaluates sedation utilization in our pediatric cardiac MR practice before and after clinical introduction of free-breathing MOCO imaging for cine and late gadolinium enhancement.Materials and Methods: In a retrospective study, patients referred for a clinical cardiac MR who would typically be offered sedation for their scan (n=295) were identified and divided into two eras, those scanned before the introduction of MOCO cine and late gadolinium enhancement sequences and those scanned following their introduction. Anesthesia use was compared across eras and disease-specific cohorts.Results: The incidence of non-sedation studies performed in children nearly tripled following the introduction of MOCO imaging (25% [pre-MOCO] to 69% [post-MOCO], P<0.01), with the greatest effect in patients with simple congenital heart disease. Eleven percent of the post-MOCO cohort comprised infants younger than 3 months of age who could forgo sedation with the combination of MOCO imaging and a "feed-and-bundle" positioning technique.Conclusion: Implementation of cardiac MR with MOCO cine and late gadolinium enhancement imaging in a pediatric population is associated with significantly decreased sedation utilization.